Rosemary Conley's Complete Flat Stomach Plan - Conley, Rosemary, 1946- (London Arrow Books, 1996)
A diet-and-exercise plan incorporating menus ranging from "instant" supermarket meals to DIY gourmet recipes, including options for vegetarians. The three separate ten-minute toning routines target the stomach and waistline, and are designed for men and women of all ages and fitness levels.
Keywords: Reducing exercises -- Weight loss